The Effect of Mandatory Disclosure on Shareholder Wealth: Evidence from FASB Statement No. 14 and ASC 280 Financial disclosures - Zabihollah Rezaee; Kingsley O Olibe (Sekolah Tinggi Manajemen IPMI, 2022)
Financial disclosures either mandatory or voluntary are essential in reducing information asymmetry between management and users of financial reports of corporations. We investigate the market’s assessment of the economic effect of geographic segment data reported under ASC 280. Specifically, this paper examines the market valuation of reported foreign assets and sales prior to and post the issuance of ASC 280. In comparing the pricing of foreign assets and foreign sales, we find that both are priced with foreign sales having greater capitalization. These results persist after controlling for other determinants and factors affecting firm value. The findings suggest that the disclosure mandated by ASC 280 enhances overall disclosure related to foreign operations and as a result makes it easier for investors to assess the value of foreign operations. These findings are consistent with management’s disclosure of improved segment information under ASC 280 and provide policy, practice, and research implications for segment reporting as well as other mandatory disclosures.